Attenuation of oxidative stress induced mitochondrial dysfunction and cytotoxicity in fibroblast cells by sulfated polysaccharide from Padina gymnospora - Vasantharaja, Raguraman; Stanley Abraham, L.; Gopinath, Venkatraman; Hariharan, D.; Smita, K.M. (Elsevier, 2019)
In this present study, isolation, characterization and protective effect of sulfated polysaccharide (SP) isolated from the brown algae Padina gymnospora was investigated. SP was isolated and characterized through FT-IR, 1H NMR, TGA, GC–MS and CHN analysis. The molecular weight of SP was found to be 16 kDa. The isolated SP contains 29.4 ± 0.35% of sulfate, 27 ± 0.11% of fucose, 0.05 ± 0.12% of protein, respectively. Furthermore, SP exhibits its excellent radical scavenging effects were evaluated by DPPH, ABTS radical scavenging and reducing power assays. Moreover, pretreatment with SP significantly mitigates H2O2 induced cytotoxicity in L-929 cells in a dose dependent manner. Furthermore, SP pretreatment ameliorates oxidative stress induced apoptosis and DNA damage, alleviates the generation of intracellular reactive oxygen species (ROS) and restores mitochondrial membrane potential (MMP) in L-929 cells through its antioxidant potential. Together, these results suggest that SP can be exploited as a natural antioxidant in the food and pharmaceutical industries.